Large branchiopods in extensive carp ponds – morphometric analysis of Triops cancriformis (Bosc, 1801) and Streptocephalus torvicornis (Waga, 1842) - Cukier Stanisław; Rączka Rafał; Kamaszewski Maciej (Oceanological and Hydrobiological Studies)
Large branchiopods is a group of poorly understood crustaceans which is highly threatened by the impact of human activities. Currently, their protection is difficult due to large deficiencies in documentation of their places of occurrence and not well researched ecology. After rediscovery of Streptocephalus torvicornis in Poland by Cukier in 2019, we conducted a survey to identify the species found at the Łąki Jaktorowskie Fisheries Research Station, Poland. This study consisted of observations and measurements of animals reared from cysts which had been obtained from soil samples taken at the nursery ponds in the study area. The following species were found: Limnadia lenticularis, Triops cancriformis, and S. torvicornis. We are presenting results of the morphometric measurements of T. cancriformis and the morphometric measurements of S. torvicornis from their only known population in Poland. Males were found in the T. cancriformis population, contrary to what has been documented previously. Large branchiopods have been repeatedly found in fishponds, and this work confirms the potentially high importance of ponds in the conservation of large branchiopods. With this study, we are drawing attention to the necessity of research about the distribution of large branchiopods in Poland.